Handling cytotoxic drugs: risk assessment - Canastro, C (2011)
Chemotherapy plays an increasingly important role in the treatment of neoplastic diseases, and there is a growing need for handling cytotoxic drugs (CTX) in hospitals. In this context, this study aimed to assess the present activity inherent risks. This assessment was carried out using two different methods, NTP330 and a new integrated assessment occupational risks and environmental impacts method. For the occupational component a comparison between two assessment methods was developed. This paper sets out the main results of the risk assessment carried out in the Oncology Pharmacy sector in a hospital center, as well as some proposals for improvements that minimize the potential exposure of workers to this Chemical Risk The achieved results allow recognition of the differences identified in the two methods evaluation and to rank the risks detected.